Síndrome de ansiedad por separación canina (ASC) (2021)
Canine separation anxiety syndrome (ASC); When very strong bonds are forged with people, it generates an excessive dependency that can make canines feel sad and painful feelings when they are separated from their caregivers. In this sense, behavior problems characterized by excessive vocalizations, destructive behaviors and / or inappropriate eliminations when the canine is left alone continue to be one of the main reasons for consulting the veterinarian. In recent years, the term separation anxiety has been used generically to describe these problems. This term implies a state of anxiety in the animal, related to the absence of the owner, which is associated with an exaggerated degree of attachment to the latter (hyperapego). However, due to clinical experience and studies carried out at the national international level in this regard, it is known that not all canines that present anxiety before the owner's departure present hyperapego, nor do all canines that have hyperapego show signs of separation anxiety (Hernández, 2012) The main objective of this study was to describe the Pathophysiology of Canine Separation Anxiety Syndrome (ASC), to know the main characteristics, diagnosis and treatment to be followed in the veterinary clinic. The methodology used for the documentary review was a descriptive study type, applying three methodological phases such as: 1. Compilation of information, 2. Classification of information and 3 Analysis of specific objectives. For this, the state of the art was conceived as the basis of argumentation of the main authors of indexed articles and studies at the international and national level that were fundamental to describe and analyze the particularities of the pathophysiology of the syndrome (ASC), determining the respective diagnosis about of behavioral disorders in canines and the appropriate treatment plan by the veterinarian. The studies clinically reported the sigmatology of the canine, for which the syndrome (ASC) should be addressed through pharmacological treatments and behavioral therapy assumed by the Veterinary doctors in time will allow an improvement and a good quality of life in the canines, providing peace of mind to their owners.